Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To determine which of the given options are solutions to the equation [tex]\(4x^2 - 12x + 9 = 5\)[/tex], we need to follow a few steps:
1. Rewriting the Equation:
Start by rewriting the equation in standard quadratic form:
[tex]\[ 4x^2 - 12x + 9 - 5 = 0 \implies 4x^2 - 12x + 4 = 0 \][/tex]
2. Simplifying the Quadratic Equation:
Simplify the quadratic equation by dividing by 4:
[tex]\[ x^2 - 3x + 1 = 0 \][/tex]
3. Solving the Quadratic Equation:
To solve the quadratic equation [tex]\(x^2 - 3x + 1 = 0\)[/tex], we can use the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 1\)[/tex], [tex]\(b = -3\)[/tex], and [tex]\(c = 1\)[/tex].
[tex]\[ x = \frac{-(-3) \pm \sqrt{(-3)^2 - 4 \cdot 1 \cdot 1}}{2 \cdot 1} \][/tex]
[tex]\[ x = \frac{3 \pm \sqrt{9 - 4}}{2} \][/tex]
[tex]\[ x = \frac{3 \pm \sqrt{5}}{2} \][/tex]
Therefore, the solutions are:
[tex]\[ x_1 = \frac{3 + \sqrt{5}}{2}, \quad x_2 = \frac{3 - \sqrt{5}}{2} \][/tex]
4. Matching Solutions with Given Options:
Now let's match each of the given options with the solutions [tex]\(x_1\)[/tex] and [tex]\(x_2\)[/tex]:
- Option A: [tex]\(x = \frac{\sqrt{5} + 3}{2}\)[/tex]
[tex]\[ \frac{3 + \sqrt{5}}{2} \quad \textit{matches} \quad x_1 = \frac{3 + \sqrt{5}}{2} \][/tex]
Therefore, Option A is a solution.
- Option B: [tex]\(x = \sqrt{4} - 3\)[/tex]
[tex]\[ \sqrt{4} - 3 = 2 - 3 = -1 \quad (\textit{This does not match} \quad x_1 \textit{ or } x_2) \][/tex]
Therefore, Option B is not a solution.
- Option C: [tex]\(x = -\sqrt{4} - 3\)[/tex]
[tex]\[ -\sqrt{4} - 3 = -2 - 3 = -5 \quad (\textit{This does not match} \quad x_1 \textit{ or } x_2) \][/tex]
Therefore, Option C is not a solution.
- Option D: [tex]\(x = -\sqrt{5} + \frac{3}{2}\)[/tex]
[tex]\[ -\sqrt{5} + \frac{3}{2} \quad (\textit{This does not match} \quad x_1 \textit{ or } x_2) \][/tex]
Therefore, Option D is not a solution.
- Option E: [tex]\(x = \sqrt{5} + \frac{3}{2}\)[/tex]
[tex]\[ \sqrt{5} + \frac{3}{2} \quad (\textit{This does not match} \quad x_1 \textit{ or } x_2) \][/tex]
Therefore, Option E is not a solution.
- Option F: [tex]\(x = \frac{-\sqrt{5} + 3}{2}\)[/tex]
[tex]\[ \frac{3 - \sqrt{5}}{2} \quad \textit{matches} \quad x_2 = \frac{3 - \sqrt{5}}{2} \][/tex]
Therefore, Option F is a solution.
In summary, the following are the solutions to the equation [tex]\(4x^2 - 12x + 9 = 5\)[/tex]:
[tex]\[A. \quad x = \frac{\sqrt{5} + 3}{2} \][/tex]
[tex]\[F. \quad x = \frac{-\sqrt{5} + 3}{2} \][/tex]
1. Rewriting the Equation:
Start by rewriting the equation in standard quadratic form:
[tex]\[ 4x^2 - 12x + 9 - 5 = 0 \implies 4x^2 - 12x + 4 = 0 \][/tex]
2. Simplifying the Quadratic Equation:
Simplify the quadratic equation by dividing by 4:
[tex]\[ x^2 - 3x + 1 = 0 \][/tex]
3. Solving the Quadratic Equation:
To solve the quadratic equation [tex]\(x^2 - 3x + 1 = 0\)[/tex], we can use the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 1\)[/tex], [tex]\(b = -3\)[/tex], and [tex]\(c = 1\)[/tex].
[tex]\[ x = \frac{-(-3) \pm \sqrt{(-3)^2 - 4 \cdot 1 \cdot 1}}{2 \cdot 1} \][/tex]
[tex]\[ x = \frac{3 \pm \sqrt{9 - 4}}{2} \][/tex]
[tex]\[ x = \frac{3 \pm \sqrt{5}}{2} \][/tex]
Therefore, the solutions are:
[tex]\[ x_1 = \frac{3 + \sqrt{5}}{2}, \quad x_2 = \frac{3 - \sqrt{5}}{2} \][/tex]
4. Matching Solutions with Given Options:
Now let's match each of the given options with the solutions [tex]\(x_1\)[/tex] and [tex]\(x_2\)[/tex]:
- Option A: [tex]\(x = \frac{\sqrt{5} + 3}{2}\)[/tex]
[tex]\[ \frac{3 + \sqrt{5}}{2} \quad \textit{matches} \quad x_1 = \frac{3 + \sqrt{5}}{2} \][/tex]
Therefore, Option A is a solution.
- Option B: [tex]\(x = \sqrt{4} - 3\)[/tex]
[tex]\[ \sqrt{4} - 3 = 2 - 3 = -1 \quad (\textit{This does not match} \quad x_1 \textit{ or } x_2) \][/tex]
Therefore, Option B is not a solution.
- Option C: [tex]\(x = -\sqrt{4} - 3\)[/tex]
[tex]\[ -\sqrt{4} - 3 = -2 - 3 = -5 \quad (\textit{This does not match} \quad x_1 \textit{ or } x_2) \][/tex]
Therefore, Option C is not a solution.
- Option D: [tex]\(x = -\sqrt{5} + \frac{3}{2}\)[/tex]
[tex]\[ -\sqrt{5} + \frac{3}{2} \quad (\textit{This does not match} \quad x_1 \textit{ or } x_2) \][/tex]
Therefore, Option D is not a solution.
- Option E: [tex]\(x = \sqrt{5} + \frac{3}{2}\)[/tex]
[tex]\[ \sqrt{5} + \frac{3}{2} \quad (\textit{This does not match} \quad x_1 \textit{ or } x_2) \][/tex]
Therefore, Option E is not a solution.
- Option F: [tex]\(x = \frac{-\sqrt{5} + 3}{2}\)[/tex]
[tex]\[ \frac{3 - \sqrt{5}}{2} \quad \textit{matches} \quad x_2 = \frac{3 - \sqrt{5}}{2} \][/tex]
Therefore, Option F is a solution.
In summary, the following are the solutions to the equation [tex]\(4x^2 - 12x + 9 = 5\)[/tex]:
[tex]\[A. \quad x = \frac{\sqrt{5} + 3}{2} \][/tex]
[tex]\[F. \quad x = \frac{-\sqrt{5} + 3}{2} \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.